Food policy research in low- and middle-income economies: Past, present, and future - Barrett, Christopher B.; DiGiovanni, Maria; Swinnen, Johan (International Food Policy Research Institute, 2025)
Food policy research can help empower consumers, producers, and policymakers to address food systems challenges and make decisions that facilitate healthy, equitable, resilient and sustainable food systems transformation. Lessons from the past 50 years of food policy can better prepare us to move forward to 2050: achieving sustainable and equitable solutions to hunger, malnutrition, and poverty will require a shift in how we study, implement, and evaluate innovations in technologies, programming, governance, investments, and markets. This chapter provides an overview of the thematic chapters of the 2025 Global Food Policy Report, which look at the impact of food policy research on agrifood transformation, sustainability, support to farmers, lives and livelihoods, and governance of food systems, and point to future challenges and opportunities.